The Relationship Between Pre-Operative Clinical Characteristics With Changes In Post-Operative Memory Scores On Temporal Lobe Epilepsy Patient - Bintoro, Aris Catur; Arifin, Muhammad Thohar; Harsono, Harsono; Muttaqin, Zainal; Hadisaputro, Soeharyo; Husni, Amin; Bakhtiar, Yuriz; Karlowe, Vega; Pratomo, Joko (RSUP Dr. Kariadi, 2023)
Background: Most temporal lobe epilepsy (TLE) will become seizure-free after anterior temporal lobectomy (ATL) surgery but often result in cognitive decline, specifically in verbal or visual memory. Objective: This study examined the relationship between several demographic characteristics and pre-operative clinical conditions with changes in pre-post surgical memory of TLE patients. Methods: This study used a retrospective cohort in which the subjects were TLE patients who had undergone ATL surgery at Kariadi Hospital or Telogorejo Hospital, Semarang. Demographic variables include the age of onset, duration of illness, level of education, and clinical variables include seizure frequency, EEG waveform, number of AED, lesion site, and IQ score. Results: Memory re-examination was conducted on TLE patients who had undergone surgery between 2018 and 2021, with 55 subjects who fulfilled the criteria. Characteristics of the subjects were male 31(56%) males, 38% Senior High School education, the mean age of onset was 13,87±6,899, age at surgery was 27,67±9,802, 21 (39%) normal pres-surgical EEG waveform, 31 (56%) lesion on the left and the most frequent seizures occurred in 36 subjects (65%). Statistical test results showed a significant relationship between age of onset and changes in verbal memory recognition scores (p 0.044), lesion side with changes in verbal memory task scores (p 0.018), recall (p 0.005), recognition (0.008), and IQ scores with changes in visual memory construction recall (p 0.041) Conclusion: Age of onset, lesion side, and IQ score characteristics were related to the changes in memory scores between pre- and post-operative anterior temporal lobectomy in TLE patients.